(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study aimed to assess the relationship between thyroid function and coronary artery disease severity. Cardiovascular disease and related mortality have emerged as a major health burden worldwide with atherosclerosis being the major cause. Thyroid dysfunction results in changes in blood pressure. The correlation between irregular thyroid function and coronary artery disease is studied by many researchers. This is a randomized, double-blinded parallel arm study with a total of 300 patients diagnosed with coronary artery disease and thyroid dysfunction. Patients were block randomised based on third-party allocation (1:1). Concealment was done through SNOSE (Sequentially Numbered Opaquely Sealed Envelope). The presence of overt hypothyroidism was significantly more in the high-risk syntax score of 28.1% compared to the intermediate risk of 17 %. The presence of subclinical hypothyroidism was significantly more in the high-risk syntax score of 18.8% compared to the intermediate risk of 11.4 %. The presence of euthyroid was significantly higher in low risk at 85.6% compared to intermediate risk at 71.6% and high risk at 53.1 %. The present study showed that Free T4 was more strongly associated with CAD and the severity of atherosclerosis than TSH in the entire study population. We conclude that Overt and Subclinical hypothyroidism patients had more severe Coronary atherosclerosis than the Euthyroid study population.